Alzheimer's disease - Landau, Elaine (New York : F. Watts, 1987)
Discusses this degenerative disease of the nervous system, its effect on the patient's family members, and suggestions for coping and care.
Includes index.
Bibliography: p. 63.
Keywords: Alzheimer's disease -- Juvenile literature; Alzheimer's disease